Observation of the chi(b1)(3P) and chi(b2)(3P) and measurement of their masses - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
The χb1ð3PÞ and χb2ð3PÞ states are observed through their ϒð3SÞγ decays, using an event sample of proton-proton collisions collected by the CMS experiment at the CERN LHC. The data were collected at a center-of-mass energy of 13 TeV and correspond to an integrated luminosity of 80.0 fb−1. The ϒð3SÞ mesons are identified through their dimuon decay channel, while the low-energy photons are detected after converting to eþe− pairs in the silicon tracker, leading to a χbð3PÞ mass resolution of 2.2 MeV. This is the first time that the J ¼ 1 and 2 states are well resolved and their masses individually measured: 10513.42 0.41ðstatÞ 0.18ðsystÞ MeV and 10524.02 0.57ðstatÞ 0.18ðsystÞ MeV; they are determined with respect to the world-average value of the ϒð3SÞ mass, which has an uncertainty of 0.5 MeV. The mass splitting is measured to be 10.60 0.64ðstatÞ 0.17ðsystÞ MeV.